Uttering the unutterable : Aristotle, religion, and literature - Groarke, Louis (McGill-Queen's University Press, 2023)
"Literature utters the unutterable, not through logic, not through science, not through argument, but through a pitch of eloquence so pronounced the conscientious reader cannot fail to pay attention. Louis Groarke argues that literature is an honorific term we use to describe texts that are so overpowering they lift us to an encounter with an ineffable ultimate that is beyond logical or scientific explanation. In Uttering the Unutterable, he proposes a wisdom epistemology that identifies an experience of transcendence as the defining criterion of literature. Offering four mutually reinforcing definitions of literature in line with Aristotle's theory of four causes, Groarke compares the experience of reading to Aristotle's account of philosophical contemplation (theoria), and maintains that literature has inevitable ethical content. Moving beyond the Aristotelianism of the late Chicago School, Groarke presents a new synthesis that breaks through essentialist stereotypes and contends that literature, like religion, points to an ineffable transcendental, to something beyond what we can adequately explain, prove, systematize, quantify, or enclose in a theory. Uttering the Unutterable explores how Aristotelian philosophy provides the most complete and compelling account of literature for philosophers, literary critics, and theorists."--